2019
DOI: 10.1128/jcm.01096-18
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Identification of Clinically Relevant Mycobacterium Species by Multicolor Melting Curve Analysis

Abstract: The sustained increase in the incidence of nontuberculous mycobacterial (NTM) infection and the difficulty in distinguishing these infections from tuberculosis constitute an urgent need for NTM species-level identification. The MeltPro Myco assay is the first diagnostic system that identifies 19 clinically relevant mycobacteria in a single reaction based on multicolor melting curve analysis run on a real-time PCR platform. The assay was comprehensively evaluated regarding its analytical and clinical performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In clinical samples, it is difficult to detect mixed infections of NTM species and to identify the species involved. The current approach, using molecular probes specific for a single gene target, has limitations, especially when it comes to species identification [ 16 , 17 ]. The presence of more than one species of NTM in cultured specimens might not be apparent from colonial morphologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical samples, it is difficult to detect mixed infections of NTM species and to identify the species involved. The current approach, using molecular probes specific for a single gene target, has limitations, especially when it comes to species identification [ 16 , 17 ]. The presence of more than one species of NTM in cultured specimens might not be apparent from colonial morphologies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no gold standard for detection and identification of multiple species infection of NTM. LPA and multiplex real-time PCR/melting curve analysis have been applied to detect mixed infections with different NTM species based on the 16S-23S rRNA intergenic transcribed spacer (ITS) region and achieved good performance using material directly from clinical samples [ 16 , 17 , 18 ]. However, the resolution of these techniques is still low because not all NTM species, especially newly discovered species, have not been included in assay development.…”
Section: Introductionmentioning
confidence: 99%
“…However, in their analysis system, the prevalent mutation IVS6+5G>A was not included, and the other three prevalent mutations were detected in three PCR reactions. In other previous studies, the real-time PCR-high resolution melting analysis was reported to be suitable for screening the presence of SLC25A13 mutations, but required further sequencing to identify the mutation types ( 25 , 26 ). Tokuhara et al ( 29 ) reported that citrin was deficient in lymphocytes among patients with citrin deficiency and Western blot analysis of citrin protein in lymphocytes isolated from peripheral blood was established as an alternative diagnostic method for citrin deficiency even in patients without known genetic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time-PCR-based multicolor melting curve analysis (MMCA) is a recently described detection method that allows the detection of multiple mutations in a single reaction, and has the benefits of speed, ease-of-use and cross-platform compatibility (22). The successful use of MMCA has been reported previously for the detection of genetic disease and pathogen typing (23)(24)(25). In this study, a novel MMCA method was developed that allows rapid screening of the four prevalent SLC25A13 mutations in one closed-tube reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have devoted their efforts in developing molecular methods to solve the problem of multiple detection in a reaction [33,34]. Currently, there are various studies focusing on the multiplex real-time PCR dissolution curve method [35,36], because the PCR dissolution curve method based on EvaGreen dye is rapid, efficient, sensitive, specific, and low cost [24,30]. e noteworthy characteristic of this methodology is the implementation of well-designed primers to make each detection target have different T m values.…”
Section: Discussionmentioning
confidence: 99%